2008
DOI: 10.3171/jns/2008/108/3/0501
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome following radical temporal bone resection for lateral skull base malignancies: a neurosurgical perspective

Abstract: The neurosurgical skull base technique could improve the probability of en bloc resection with a tumor-free margin for extensive temporal bone malignancies, which would cure a subset of patients. The active participation of neurosurgeons would improve patient care in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 38 publications
(54 reference statements)
0
26
0
1
Order By: Relevance
“…These numbers are reflections of the underlying characteristics of the patient cohort at each institution. 815,1719,22,23,30–32,34,35,3742 Attempting to improve understanding of prognostic factors, 5 groups have recently analyzed outcomes using univariate analyses. In 1997, Testa et al 20 reported outcomes of 79 Brazilian patients treated between 1953 and 1995.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are reflections of the underlying characteristics of the patient cohort at each institution. 815,1719,22,23,30–32,34,35,3742 Attempting to improve understanding of prognostic factors, 5 groups have recently analyzed outcomes using univariate analyses. In 1997, Testa et al 20 reported outcomes of 79 Brazilian patients treated between 1953 and 1995.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature consists of numerous case series that have reported a wide range of survival data, reflecting differences in the underlying characteristics of cohorts drawn from various institutions. 1,6,[8][9][10][12][13][14][15]18,19,22,24,[30][31][32][33][34][35][36][37][38][39][40][41] Historical survival data can be most readily generalized to clinical practice if factors predictive of outcome can be identified. Several larger series have reported preliminary descriptions of factors influencing survival, based on univariate comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are reflections of the underlying characteristics of the patient cohort at each institution. [8][9][10][11][12][13][14][15][17][18][19]22,23,[30][31][32]34,35,[37][38][39][40][41][42] Attempting to improve understanding of prognostic factors, 5 groups have recently analyzed outcomes using univariate analyses. In 1997, Testa et al 20 Based on these outcomes data, we currently consider the minimum operation for the vast majority of malignant disease involving the external auditory canal/temporal bone to be a lateral temporal bone resection.…”
Section: Discussionmentioning
confidence: 99%
“…A su vez, como sabemos, la elección óptima del abordaje quirúrgico también dependerá del proceso patológico en cuestión (1,2,3) . Los abordajes quirúrgicos tradicionales al ápex orbitario incluyen, entre otros, orbitotomías laterales y craneotomías con componente orbitario, ambos procedimientos muy invasivos y con significativa morbilidad si los comparamos a los empleados en los abordajes quirúrgicos endoscópicos (4,5,6,7,1,8) . Además de los clásicos, otros tipos de abordajes posibles a esta región son los endoscópicos tansetmoidales y transmaxilares.…”
Section: Introductionunclassified